Arsenic and toxic metals in meat and fish consumed in Niger delta, Nigeria: Employing the margin of exposure approach in human health risk assessment. (January 2022) - Okoye, Esther Amaka; Bocca, Beatrice; Ruggieri, Flavia; Ezejiofor, Anthonett N.; Nwaogazie, Ify L.; Frazzoli, Chiara; Orisakwe, Orish E.
Abstract: This study provides information on the health risk of As, Cd, Hg, Pb and V exposure from Nigerian foods consumption (fish, cow, goat and chicken meat) in different age-groups (children, adolescent, adult, senior) and six areas of Niger Delta, Nigeria (Choba, Khana, Eleme, TransAmadi, Uyo, and Yenogoa). The health risk assessment was performed by estimating the weekly or monthly intake of metals from foods and Margin of Exposure (MOE) approach by using established benchmark dose levels (BMDLs). Regarding As, cow and chicken meat products contributed to As exposure intake especially in children resulting in values higher than BMDL0.1 for cancer risk in TransAmadi and Uyo areas. Cadmium exposure was due to cow, chicken and goat meat ingestion mostly in adolescent above the tolerable monthly intake limit in TransAmadi and Uyo areas. Concerning Hg and V, the exposure from Nigerian food did not constitute a potential health hazard. Lead exposure in children were above or close to BMDL0.1 for developmental neurotoxicity by ingestion of cow and goat meat in all the Nigerian areas. In adult and senior the Pb dietary exposure were above the BMDL10 providing a low to negligible risk for kidney effects. The potential concern for health effects in Niger Delta population needs further efforts to decrease As, Cd and Pb dietary exposure especially for children and adolescent, who are more vulnerable to adverse life events. Highlights: Dietary exposure data of As, Cd, Hg, Pb and V from commonly Nigerian foods consumption were assessed by PTWI or PTMI calculation. Health risk characterization was explored by MOE approach. At current dietary levels of As and Pb, the potential concern for effects in children was not negligible. Food products did not constitute a possible source of human exposure to Hg and V.